AN IMPROVED CANOPY INTERCEPTION SCHEME INTO BIOGEOCHEMICAL ANALYSIS OF WATER FLUXES IN SUBALPINE CONIFEROUS FOREST (NORTHERN ITALY) - Lemenkova, Polina (Bulletin of Natural Sciences Research, 2025)
The delicate ecosystems of the Alps' subalpine forests are crucial to water supplies as well as the local and mesoscale climate regulators. Although earlier research has assessed various aspects of the water balance, there is currently a dearth of studies that directly measure every component of the water budget. Furthermore, little is understood about the frequency and impact of fog as well as how forest layout affects water balance. Using the eddy covariance technique, sap flow sensors, phenocam images, throughfall and stemflow gauges, soil moisture sensors, water discharge measurements, and a fog interception gauge, we carried out a thorough investigation of a subalpine coniferous forest at the Renon site in the Italian Alps.  Furthermore, we measured the leaf area and lichen occurrence as possible canopy water storage components. Large amount of precipitation was reflected by the canopy interception in spruce and coniferous forest. Although fog alone had no effect on total water intake, it did result in a tiny but noticeable increase in throughfall during mixed fog and rain precipitation events, however this effect seemed to be less significant than in cloud forests that are tropical or subtropical. At the catchment level, the annual balance (November–October) was almost perfectly closed when all input and output components were taken into account. This paper contributes to the ecological monitoring of the Alpine forests in South Tyrol, Northern Italy.
Keywords: Fog; Canopy Interception; Evaporation; Throughfall; Forest; Rainfall; Northern Italy